Biomass full-spectrum response type indoor air purification material and preparation method thereof

By transforming oyster shells into a composite air purification material with enhanced photocatalytic and antibacterial properties, the material addresses waste pollution and indoor air quality issues, providing efficient and wide-spectrum air purification.

CN119909643APending Publication Date: 2025-05-02HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510256936.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The accumulation of oyster shell waste poses environmental pollution and health risks due to odor and microbial growth, while indoor air quality issues, particularly VOCs and microbial contamination, threaten human health, necessitating effective air purification solutions.

Method used

A biowaste-derived oyster shell material is transformed into a composite air purification material through a series of chemical and thermal processes, incorporating ZnO/HAP, (Ca,Y)F2:Tm,Yb, and N-doped TiO2, enhancing its photocatalytic and antibacterial properties for comprehensive air purification.

Benefits of technology

The material effectively degrades VOCs and inhibits microbial growth, offering high-efficiency, broad-spectrum air purification with improved photocatalytic and antibacterial performance under various light conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909643A_ABST
    Figure CN119909643A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass full-spectrum response type indoor air purification material and a preparation method thereof, and relates to the field of building functional materials, biomass waste oyster shells are used as raw materials, hydroxyapatite is prepared by a water bath method, hydroxyapatite is used as a carrier, and a ZnO / HAP composite material is prepared by dipping, calcining and other methods. The preparation method comprises the following steps: preparing an up-conversion luminescent material (Ca, Y) F2: Tm, Yb, doping the up-conversion luminescent material with visible-light response type N-doped TiO2 (JR05) in the market to obtain a JR05 / (Ca, Y) F2: Tm, Yb composite material, doping the material with ZnO / HAP, and finally preparing the composite material JR05 / (Ca, Y) F2: Tm, Yb / ZnO / HAP. The material is an indoor building functional material and is used for indoor air purification. The material not only has good adsorption and degradation effects on methyl orange and formaldehyde, but also has good antibacterial performance, the spectral response range is widened, full-spectral response can be realized, the photocatalytic degradation and antibacterial performance of the material can be greatly improved under illumination, and the material has good application prospects. The problem of biomass waste pollution can be solved to a certain extent, and the indoor air environment can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of novel building functional materials, in particular to a biomass full-spectrum responsive indoor air purification material and a preparation method thereof. Background Art

[0002] With the continuous development of my country's fishery, the survey of "China Fisheries Statistical Yearbook 2024" shows that in 2023, the output of oyster aquaculture in my country will reach 6,671,197 tons, a year-on-year increase of 7.61%, and the area of ​​oyster aquaculture in seawater will reach 276,816 hectares, a year-on-year increase of 17.82%. As a result, a large amount of oyster shell biomass waste will be generated. The accumulation of these wastes will occupy a large amount of space, produce odors and breed pathogenic microorganisms, which will not only cause environmental pollution but also pose a huge potential threat to people's health. Therefore, it is an important means to efficiently use oyster shells to turn waste into treasure and realize solid waste utilization.

[0003] The quality of indoor air environment is closely related to the health of indoor personnel. Various decorative materials have made indoor air pollution increasingly serious. The discovery of building-related diseases such as sick building syndrome (SBS) has further attracted people's attention to indoor air environment issues, and indoor air environment purification has gradually become a hot topic of concern. Indoor air pollutants such as volatile organic compounds (VOCs), bacteria and viruses can affect human health. Most VOCs are important factors causing building syndrome. VOCs can irritate the eyes, nose and throat, and more seriously can cause dizziness, headaches, memory and visual impairment, and even death. Among them, VOCs such as formaldehyde, acetaldehyde, acetone and acrolein have been proven to cause serious health risks, and pollution from microorganisms such as bacteria and viruses can also cause great harm to the indoor air environment and human health.

[0004] Photocatalytic technology can decompose organic pollutants in the air into carbon dioxide and water. It has the characteristics of mild reaction conditions, high purification efficiency, multiple applicable scenarios, and no secondary pollution. It is widely used to purify indoor air pollutants. Antibacterial materials are a new type of functional materials that have the function of inhibiting or killing microorganisms (such as bacteria, viruses, etc.), which can hinder the growth of bacteria or even kill bacteria.

[0005] Hydroxyapatite (HAP) is a calcium phosphate mineral with the chemical formula of Ca10(PO4)6(OH)2. It is odorless, non-toxic, stable, and has good mechanical properties. It is the main component of bones and teeth. Hydroxyapatite has a large specific surface area and good adsorption capacity, and can be used as an adsorption material and carrier.

[0006] The present invention is based on solving the pollution of oyster shell biomass waste and indoor air purification. The biomass waste oyster shell is used as raw material, hydroxyapatite (HAP) is prepared by a water bath method, and HAP is used as a carrier to prepare a ZnO / HAP composite material by impregnation, calcination and other methods. The upconversion luminescent material (Ca, Y) F2: Tm, Yb is prepared by hydrothermal, calcination and other methods, and it is doped with visible light responsive N-doped TiO2 (JR05) to obtain a JR05 / (Ca, Y) F2: Tm, Yb composite material, and then it is doped with ZnO / HAP to finally prepare a new building functional composite material, and the photocatalytic degradation ability of the material to methyl orange, the adsorption and degradation ability to formaldehyde, and the inhibition ability to Escherichia coli and Staphylococcus aureus are tested. Summary of the invention

[0007] The purpose of the present invention is to solve the environmental pollution caused by biomass waste oyster shells, realize solid waste utilization, and develop a full-spectrum responsive composite air purification material with a synergistic air purification mechanism to effectively improve the indoor air environment.

[0008] In order to solve the current technical problems, the present invention provides a method for preparing a biomass full-spectrum responsive indoor air purification material. The technical solution includes the following steps:

[0009] Step (1) cleaning, drying and grinding oyster shells into powder, immersing 1 to 30 g of oyster shell powder in 20 to 500 mL of (NH4)2HPO4 solution, then adding 1 to 10 mL of NaOH solution to adjust the pH value of the solution to 9 to 10, and finally placing the solution in a water bath at 80 to 90° C. and stirring for 6 to 8 hours, and obtaining oyster shell-modified hydroxyapatite (HAP) powder after centrifugation, washing, drying and grinding;

[0010] Step (2) immersing 3 to 9 g of the hydroxyapatite powder prepared in step (1) in 80 to 300 mL of a Zn(CH3COO)2·2H2O solution, adding 1 to 4 g of Na2CO3 powder after magnetic stirring for 3 to 6 hours, continuing magnetic stirring for 4 to 7 hours, centrifuging, washing, drying, and grinding, placing in a muffle furnace, and calcining at 400 to 500° C. for 3 to 5 hours to obtain a ZnO / HAP composite material.

[0011] Step (3) Add 20-80 mL of deionized water to a 150 mL beaker, then add 0.1-0.6 g of anhydrous calcium chloride (CaCl 2) and 0.02-0.1 g of PVP (polyvinyl pyrrolidone), stir magnetically for 15-30 min, then add 0.2-1 mL of TmCl 3·6H2O solution, 1-5 mL of YbCl 3·6H2O solution, 2-10 mL of YCl 3.6H2O solution; continue stirring for 15 to 30 minutes, then slowly add 5 to 20 mL of 0.15 to 0.7 g of NH4F solution drop by drop, stir for 2 to 3 hours, then put the mixed solution into a stainless steel high-pressure reactor, hydrothermally react at 160 to 190°C for 10 to 14 hours, centrifugally wash, dry and grind, then put it into a muffle furnace and calcine at 400 to 600°C for 4 to 6 hours to obtain (Ca, Y)F2:Tm,Yb upconversion luminescent material.

[0012] Step (4) co-doping 1-10 g of commercially available visible light responsive N-doped TiO2 (JR05) with 2-20 g of the (Ca, Y)F2: Tm, Yb upconversion luminescent material prepared in step (3) to obtain a full-spectrum responsive TiO2 high-efficiency photocatalytic material JR05 / (Ca, Y)F2: Tm, Yb.

[0013] Step (5) doping 1-10 g of the JR05 / (Ca, Y)F2:Tm, Yb material prepared in step (4) with 2-20 g of the ZnO / HAP powder prepared in step (2), and after sufficient grinding, obtaining a JR05 / (Ca, Y)F2:Tm, Yb / ZnO / HAP biomass full-spectrum responsive composite air purification material.

[0014] Preferably, in the step (1), the Ca / P molar ratio of oyster shell powder to diammonium hydrogen phosphate is 1.67, the concentration of (NH4)2HPO4 solution is 0.1-0.5 mol / L, the concentration of NaOH solution is 0.5-1.5 mol / L, the centrifugal speed is 10000 rpm, the centrifugal time is 5-10 min, the washing is cross-washed with deionized water and anhydrous ethanol 1-2 times, and the oyster shell and hydroxyapatite powder are dried in an oven at 60-80°C for 8-14 h.

[0015] Preferably, in the step (2), the concentration of the Zn(CH3COO)2·2H2O solution is 0.1-0.3 mol / L, the magnetic stirring speed is 400-600 r / min, the centrifugal speed is 10000 rpm, the centrifugal time is 5-10 min, the washing is cross-washed with deionized water and anhydrous ethanol 2-3 times, the material is dried in an oven at 60-80°C for 10-15 h, and the muffle furnace heating rate is 5-10°C / min.

[0016] Preferably, in the step (3), the concentration of the TmCl 3·6H2O solution is 10 μmol / mL, the concentration of the YbCl 3·6H2O solution is 0.1 mmol / mL, the concentration of the YCl 3·6H2O solution is 0.2 mmol / mL, the concentration of the NH4F solution is 0.874 mmol / L, the centrifugal speed is 10000 rpm, the centrifugal time is 5 to 10 min, the washing is cross-washed with deionized water and anhydrous ethanol 2 to 3 times, the material is dried in an oven at 60 to 80°C for 10 to 15 h, and the muffle furnace heating rate is 5 to 10°C / min.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The present invention uses oyster shells, a biomass waste, as raw materials and modifies them into hydroxyapatite with a larger specific surface area and a more porous structure through a water bath method. The hydroxyapatite has stronger adsorption and loading capacity and can alleviate the environmental pollution problem caused by biomass waste to a certain extent.

[0019] (2) This material can not only realize the resource utilization of biomass solid waste, but also has the synergistic air purification functions of adsorption, antibacterial and photocatalytic degradation, which improves the purification efficiency and can achieve a more efficient and lasting improvement in indoor air quality.

[0020] (3) This material not only has a good adsorption and degradation effect on methyl orange and formaldehyde, but also has good antibacterial properties. In addition, this material has a broadened spectral response range and can achieve full spectrum response, which greatly improves its photocatalytic degradation effect and antibacterial properties under light. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is the X-ray diffraction pattern of hydroxyapatite modified with biomass waste oyster shells prepared in Example 1;

[0023] Figure 2 This is a scanning electron micrograph of the ZnO-loaded hydroxyapatite modified with discarded oyster shells prepared in Example 2;

[0024] Figure 3This is the fluorescence spectrum of the up-conversion luminescent material (Ca, Y) F2: Tm, Yb prepared in Example 5;

[0025] Figure 4 This is a Fourier infrared spectrum of the full-spectrum responsive composite air purification material prepared in Example 6;

[0026] Figure 5 is a graph showing the degradation and removal rate of methyl orange by the composite materials prepared in Examples 6 to 8 under sunlight;

[0027] Figure 6 is a graph showing the degradation removal rate of methyl orange by the composite materials prepared in Examples 6 to 8 under ultraviolet light;

[0028] Figure 7 is a graph showing the degradation removal rate of methyl orange by the composite materials prepared in Examples 6 to 8 under visible light;

[0029] Figure 8 It is a graph showing the degradation removal rate of methyl orange by the composite materials prepared in Examples 6 to 8 under near infrared light;

[0030] Fig. 9 The figure is a curve diagram of the formaldehyde removal rate of the composite materials prepared in Examples 6 to 8. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] This embodiment provides a preparation method for modifying biomass waste oyster shells into hydroxyapatite (HAP), comprising the steps of:

[0034] (1) In a 300 mL beaker, add deionized water and prepare 200 mL of 0.3 mol / L (NH4)2HPO4 solution, immerse 10 g of oyster shell powder in the solution, and stir magnetically at 500 r / min for 10 min;

[0035] (2) In a 50 mL beaker, add deionized water and prepare 10 mL of 1 mol / L NaOH solution, add all of the solution to the solution in step (2), continue stirring for 10 min, then place the beaker containing the mixed solution in a 90°C constant temperature water bath and continue stirring at 500 r / min for 7 h;

[0036] (3) After step (2), the sample was taken out of the water bath, cooled naturally to room temperature, centrifuged at 10,000 rpm for 5 min, cross-washed twice with deionized water and anhydrous ethanol, and dried in an oven at 60°C for 15 h to obtain oyster shell-modified hydroxyapatite (HAP).

[0037] Figure 1 This is the X-ray diffraction pattern of the hydroxyapatite modified by biomass waste oyster shell prepared in Example 1. It can be seen that the prepared hydroxyapatite has good crystallinity, the sample diffraction peak is sharp, and there are no other miscellaneous peaks.

[0038] Example 2

[0039] This embodiment provides a method for preparing hydroxyapatite loaded with ZnO, comprising the steps of:

[0040] (1) 3 g of the hydroxyapatite powder prepared in Example 1 was immersed in 100 mL of 0.0369 mol / L Zn(CH3COO)2·2H2O solution and magnetically stirred at room temperature for 3 h at 500 r / min;

[0041] (2) After step (3), 0.39 g of anhydrous sodium carbonate (Na2CO3) powder was added to the solution, and the mixture was stirred for 4 h, then centrifuged at 10,000 rpm for 5 min, and washed twice with deionized water and anhydrous ethanol, and the sample was dried in an oven at 60 °C for 15 h;

[0042] (3) After step (3), the sample was ground into powder, placed in a muffle furnace, the temperature was increased at a rate of 5°C / min, and calcined at 400°C for 3h to obtain an oyster shell-modified hydroxyapatite-loaded ZnO composite material ZnO / HAP.

[0043] Figure 2 This is a scanning electron microscope image of the hydroxyapatite loaded with ZnO modified by the waste oyster shell prepared in Example 2. It can be seen that the prepared hydroxyapatite is stacked by a large number of irregular flakes and rod-shaped particles, and the surface of the hydroxyapatite is relatively evenly loaded with spherical nano ZnO particles, and the particle size of the nano ZnO particles is maintained at about 30 to 50 nm.

[0044] Example 3

[0045] The other steps are the same as those in Example 2, except that 3 g of the hydroxyapatite powder prepared in Example 1 is immersed in 100 mL of 0.0369 mol / L Zn(CH3COO)2·2H2O solution, and the concentration of the solution is changed from 0.0369 mol / L to 0.11 mol / L; and the weight of 0.39 g of anhydrous sodium carbonate (Na2CO3) powder added to the solution is changed from 0.39 g to 1.172 g.

[0046] Example 4

[0047] The other steps are the same as those in Example 2, except that 3 g of the hydroxyapatite powder prepared in Example 1 is immersed in 100 mL of 0.0369 mol / L Zn(CH3COO)2·2H2O solution, and the concentration of the solution is changed from 0.0369 mol / L to 0.184 mol / L; and the weight of 0.39 g of anhydrous sodium carbonate (Na2CO3) powder added to the solution is changed from 0.39 g to 1.9532 g.

[0048] Table 1 is a comparison of the relevant parameters of the materials prepared by Examples 1 to 4

[0049]

[0050] Example 5

[0051] This embodiment provides a method for preparing an up-conversion luminescent material (Ca, Y) F2: Tm, Yb, comprising the steps of:

[0052] (1) Add 80 mL of deionized water to a 300 mL beaker, take 0.552 g of anhydrous CaCl 2 and 0.1 g of PVP powder and add them to the beaker, and stir magnetically at room temperature at 400 r / min for 20 min;

[0053] (2) Add 1 mL of 10 μmol / mL TmCl 3·6H2O solution, 5 mL of 0.1 mmol / mL YbCl 3·6H2O solution, and 10 mL of 0.2 mmol / mL YCl 3·6H2O solution to the solution in step (1), and continue stirring for 20 min;

[0054] (3) Prepare 20 mL of 0.874 mmol / L NH4F solution, slowly add the solution dropwise to the solution in step (2), and then continue stirring at 400 r / min for 2 h;

[0055] (4) After step (3), the mixed solution was placed in a stainless steel autoclave, placed in an electric constant temperature drying oven, and subjected to hydrothermal reaction at 180°C for 12 hours. After the reaction, it was cooled to room temperature, centrifuged at 10,000 rpm for 5 minutes, and cross-washed twice with deionized water and anhydrous ethanol, and then placed in a 60°C oven for 12 hours. After drying, the sample was ground into powder, placed in a muffle furnace and calcined at 500°C for 5 hours, with a muffle furnace heating rate of 5°C / min, and finally (Ca, Y) F2: Tm, Yb upconversion luminescent material was obtained.

[0056] Figure 3 This is the fluorescence spectrum of the up-conversion luminescent material (Ca, Y) F2: Tm, Yb prepared in Example 5. Under the excitation of 980nm near-infrared light, the sample emits ultraviolet light at 360nm and visible light at 467nm and 653nm.

[0057] Example 6

[0058] This embodiment provides a method for preparing a full-spectrum responsive composite air purification material, comprising the steps of:

[0059] (1) 10 g of commercially available visible light responsive N-doped TiO2 (JR05) was doped with 20 g of the upconversion luminescent material prepared in Example 5, and after sufficient grinding, a full-spectrum responsive TiO2 high-efficiency photocatalytic nanomaterial JR05 / (Ca, Y)F2: Tm, Yb was obtained;

[0060] (2) 10 g of the full-spectrum responsive composite material prepared in step (1) is doped with 10 g of the material prepared in Example 3, and after sufficient grinding, a full-spectrum responsive composite air purification material JR05 / (Ca, Y)F2:Tm, Yb / ZnO / HAP is obtained.

[0061] Figure 4 This is the Fourier infrared spectrum of the full-spectrum responsive composite air purification material prepared by Example 6. It can be seen that 3436 cm-1 is the stretching vibration peak of OH adsorbed water, 1468 cm-1 is the stretching vibration peak of C=O, 567.18 cm-1, 604.93 cm-1 and 1038 cm-1 are the stretching vibration peaks of the PO bond in PO3-4, 567.18 cm-1 and 604.93 cm-1 are the bending vibration peaks of the OPO bond, 874 cm-1 is the stretching vibration peak of CO, and 447.01 cm-1 is the stretching vibration peak of Zn-O.

[0062] Example 7

[0063] The other steps are the same as those of Example 6, except that the weight of the material doped with 10 g of the material prepared in Example 3 in step (2) is changed from 10 g to 20 g.

[0064] Example 8

[0065] The other steps are the same as those of Example 6, except that the weight of the material doped with 10 g of the material prepared in Example 3 in step (2) is changed from 10 g to 30 g.

[0066] Table 2 is a comparison of the relevant parameters of the materials prepared by Examples 6 to 8

[0067]

[0068]

[0069] Experimental example

[0070] 1. Using a 500W xenon lamp as the light source, the photocatalytic performance of the composite materials prepared in Examples 6 to 8 was tested by replacing the filters to simulate sunlight, ultraviolet light, visible light and near-infrared light, respectively. Methyl orange solution was used as the target pollutant. The test steps included: taking 50mL of 10mg / L organic dye methyl orange solution into a 150mL beaker, adding 150mg of the composite materials in Examples 6 to 8, first magnetically stirring for 30min under dark conditions to achieve adsorption and desorption equilibrium, and then performing a photocatalytic degradation experiment. The beaker was placed in a constant temperature magnetic stirrer, and the distance between the light source and the liquid surface was adjusted to 15cm. Samples were taken every 30min, the samples were centrifuged to obtain the supernatant, and its absorbance was measured using a UV1200 ultraviolet-visible spectrophotometer.

[0071] Figures 5 to 8 The degradation removal rate curves of methyl orange by the composite materials prepared in Examples 6 to 8 under sunlight, ultraviolet light, visible light and near-infrared light.

[0072] 2. The composite materials prepared in Examples 6 to 8 were subjected to formaldehyde removal test, and the test steps included: placing a high-precision formaldehyde detector and a fan in a 0.7m×0.6m×0.5m structural test closed cabin, and taking a formaldehyde solution with a mass fraction of 37% as the target pollutant. Take 3g of the composite materials prepared in Examples 6 to 8 and evenly spread them in a culture dish with a diameter of about 9cm, and cover it with a plexiglass sheet, take 20μL of formaldehyde solution and drop it on the filter paper, put it in the cabin and blow it with a fan for 30min to completely volatilize the formaldehyde solution, after the formaldehyde concentration in the cabin is balanced, remove the glass sheet on the culture dish and start the test, and record the formaldehyde concentration value in the cabin every 5min.

[0073] Fig. 9 The formaldehyde removal rate curve of the composite materials prepared in Examples 6 to 8.

[0074] 3. The composite materials prepared in Examples 1 to 4 and 6 to 8 were tested for antibacterial properties. The test steps included: referring to the test method in GB / T21510-2008 "Nano-inorganic material antibacterial property test method", testing the antibacterial effect of the composite materials on Escherichia coli (E.co li) and Staphylococcus aureus (S.aureus). The inhibitory effect on bacteria is shown in Table 3 below, and the antibacterial effect is the average value of 3 experiments.

[0075]

[0076] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a biomass full-spectrum responsive indoor air purification material, characterized in that: The following steps are involved: Step (1) cleaning, drying and grinding oyster shells into powder, immersing 1 to 30 g of oyster shell powder in 20 to 500 mL of (NH4)2HPO4 solution, then adding 1 to 10 mL of NaOH solution to adjust the pH value of the solution to 9 to 10, and finally placing the solution in a water bath at 80 to 90° C. and stirring for 6 to 8 hours, and obtaining oyster shell-modified hydroxyapatite (HAP) powder after centrifugation, washing, drying and grinding; Step (2) immersing 3 to 9 g of the hydroxyapatite powder prepared in step (1) in 80 to 300 mL of a Zn(CH3COO)2·2H2O solution, adding 1 to 4 g of Na2CO3 powder after magnetic stirring for 3 to 6 hours, continuing magnetic stirring for 4 to 7 hours, centrifuging, washing, drying, and grinding, placing in a muffle furnace, and calcining at 400 to 500° C. for 3 to 5 hours to obtain a ZnO / HAP composite material; Step (3) Add 20-80 mL of deionized water to a 150 mL beaker, then add 0.1-0.6 g of anhydrous calcium chloride (CaCl 2) and 0.02-0.1 g of PVP (polyvinyl pyrrolidone), stir magnetically for 15-30 min, then add 0.2-1 mL of TmCl 3·6H2O solution, 1-5 mL of YbCl 3·6H2O solution, 2-10 mL of YCl 3.6H2O solution; continue stirring for 15 to 30 minutes, slowly add 5 to 20 mL of 0.15 to 0.7 g of NH4F solution drop by drop, stir for 2 to 3 hours, then put the mixed solution into a stainless steel high-pressure reactor, hydrothermally react at 160 to 190°C for 10 to 14 hours, centrifugally wash, dry and grind, put it into a muffle furnace and calcine at 400 to 600°C for 4 to 6 hours to obtain (Ca, Y)F2:Tm,Yb upconversion luminescent material; Step (4) co-doping 1-10 g of commercially available visible light responsive N-doped TiO2 (JR05) with 2-20 g of the (Ca, Y) F2: Tm, Yb upconversion luminescent material prepared in step (3) to obtain a full-spectrum responsive TiO2 high-efficiency photocatalytic material JR05 / (Ca, Y) F2: Tm, Yb; Step (5) doping 1-10 g of the JR05 / (Ca, Y)F2:Tm, Yb material prepared in step (4) with 2-20 g of the ZnO / HAP powder prepared in step (2), and after sufficient grinding, obtaining a JR05 / (Ca, Y)F2:Tm, Yb / ZnO / HAP biomass full-spectrum responsive composite air purification material.

2. The method for preparing a biomass full-spectrum responsive indoor air purification material according to claim 1, characterized in that: In the step (1), the Ca / P molar ratio of oyster shell powder to diammonium hydrogen phosphate is 1.67, the concentration of (NH4)2HPO4 solution is 0.1-0.5 mol / L, the concentration of NaOH solution is 0.5-1.5 mol / L, the centrifugal speed is 10000 rpm, the centrifugal time is 5-10 min, the washing is cross-washed with deionized water and anhydrous ethanol 1-2 times, and the oyster shell and hydroxyapatite powder are dried in an oven at 60-80°C for 8-14 h.

3. The method for preparing a biomass full-spectrum responsive indoor air purification material according to claim 1, characterized in that: In the step (2), the concentration of the Zn(CH3COO)2·2H2O solution is 0.1-0.3 mol / L, the magnetic stirring speed is 400-600 r / min, the centrifugal speed is 10000 rpm, the centrifugal time is 5-10 min, the washing is cross-washed with deionized water and anhydrous ethanol 2-3 times, the material is dried in an oven at 60-80°C for 10-15 h, and the muffle furnace heating rate is 5-10°C / min.

4. The method for preparing a biomass full-spectrum responsive indoor air purification material according to claim 1, characterized in that: In the step (3), the concentration of the TmCl 3·6H2O solution is 10 μmol / mL, the concentration of the YbCl 3·6H2O solution is 0.1 mmol / mL, the concentration of the YCl 3·6H2O solution is 0.2 mmol / mL, the concentration of the NH4F solution is 0.874 mmol / L, the centrifugal speed is 10000 rpm, the centrifugal time is 5 to 10 min, the washing is cross-washed with deionized water and anhydrous ethanol 2 to 3 times, the material is dried in an oven at 60 to 80° C. for 10 to 15 h, and the muffle furnace heating rate is 5 to 10° C. / min.

5. An air purification material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The material has an adsorption and degradation effect on formaldehyde. Under sunlight, ultraviolet light, visible light and near-infrared light simulated by a 500W xenon lamp, it has a degradation effect on methyl orange solution and has an inhibitory effect on Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli).